1995
DOI: 10.1007/bf00749397
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the 31 kDa cytosolic phospholipase A2, as an antigen recognized by the lung cancer-specific human monoclonal antibody, AE6F4

Abstract: The human monoclonal antibody AE6F4 specifically reacts with human lung cancer tissues but does not with normal tissues. This monoclonal antibody recognizes a cytosolic 31 kDa antigen in the cancer cells. In a previous study, we elucidated that the 31 kDa antigen belonged to a family of proteins collectively designated as 14-3-3 proteins, which were known as protein kinase-dependent activators of tyrosine/trytophan hydroxylases, or protein kinase C inhibitor proteins. Here we report molecular cloning of the 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…As shown in Figure 1, the 31 kDa antigen in the soluble fraction, 53 and 40 kDa antigens in insoluble fraction were detected by AE6F4 antibody. These antigens were previously reported 14-3-3 proteins (Shoji et al, 1994a;Kawamoto et al, 1995), CK8 and CK19 (Ichikawa et al, 1997), respectively. To confirm whether carbohydrate chains in these antigens participate in antigen recognition by AE6F4 antibody, the protein-transferred nitrocellulose membrane was treated with sodium periodate to destruct the carbohydrate chain structure.…”
Section: Reactivity Of Ae6f4 Antibody To Mcf-7 Cell Extractsupporting
confidence: 73%
See 2 more Smart Citations
“…As shown in Figure 1, the 31 kDa antigen in the soluble fraction, 53 and 40 kDa antigens in insoluble fraction were detected by AE6F4 antibody. These antigens were previously reported 14-3-3 proteins (Shoji et al, 1994a;Kawamoto et al, 1995), CK8 and CK19 (Ichikawa et al, 1997), respectively. To confirm whether carbohydrate chains in these antigens participate in antigen recognition by AE6F4 antibody, the protein-transferred nitrocellulose membrane was treated with sodium periodate to destruct the carbohydrate chain structure.…”
Section: Reactivity Of Ae6f4 Antibody To Mcf-7 Cell Extractsupporting
confidence: 73%
“…Shoji et al revealed that the AE6F4 antibody recognizes a 31 kDa antigen in the cytosolic fraction of A549 cells and partial amino acid sequence of this 31 kDa antigen shows a 90% homology to the 14-3-3 protein family (Shoji et al, 1994b). Kawamoto et al reported that the 31 kDa antigen cDNA cloned from A549 cells is identical to cytosolic phospholipase A2 (cPLA2) which is a member of the 14-3-3 protein family (Kawamoto et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cPLA2 expression is increased in several human cancers including small bowel, lung, bile duct and liver [12,23-25]. Proliferation of prostate cancer is also dependant on the action of cPLA2 [26].…”
Section: Discussionmentioning
confidence: 99%
“…BD9D12 and AE6F4 hybridoma cell lines were established by an in vitro immunization method (Kawahara et al, 1992). AE6F4 mAb recognizes 14-3-3 protein in lung cancer cells (Shoji et al, 1994a;1994b;Kawamoto et al, 1995) and cytokeratin 8 (Ichikawa et al, 1997). HB4C5 mAb has been applied to RI imaging of lung cancer tissues (Kusakabe et al, 1994) and AE6F4 to diagnosis of lung cancer cells in sputa (Shoji et al, 1994a).…”
Section: Introductionmentioning
confidence: 99%